Cold-rolled steel sheet and method for producing same
By optimizing the composition and heat treatment process in cold-rolled steel plates, a specific microstructure is formed, and the balance problem between the moldability and elongation of ultra-high strength steel is solved, achieving tensile strength of 980MPa to 1180MPa and 23% to 25 The elongation of % improves the moldability and weldability of automotive steel plates.
Patent Information
- Application Number
- CN202280095687.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-03
- Filing Date
- 2022-12-05
- Publication Date
- 2024-12-13
AI Technical Summary
The moldability of existing ultra-high strength steels decreases with increasing strength, making it difficult to achieve an excellent balance between high strength and high elongation, especially in the development of automotive steel plates.
Cold rolling by designing a cold rolling containing 0.15% to 0.20% carbon, 1.0% to 2.0% silicon, 1.5% to 3.0% manganese, 0.01% to 0.3% aluminum and 48/14·[N] to 0.1% titanium The steel plate, whose final microstructure consists of ferrite, needle-like residual austenite, martensite/austeinite composite structure and block-like martensite, and adopts a specific heat treatment process, including two annealing and over-aging steps , ensure that the area fraction of ferrite is between 30% and 60%, the needle-like residual austenite is between 5% and 12%, and the martensite/austeinetic composite structure is between 25% and 50%.
Tensile strength of 980MPa to 1180MPa and elongation of 23% to 25%, ensuring excellent moldability and processability while improving weldability.
Smart Images

Figure CN119137301A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cold-rolled steel sheet and a method for manufacturing the same, and more particularly to a cold-rolled ultra-high strength low-carbon steel sheet with excellent formability and a method for manufacturing the same. Background Art
[0002] Ultra-high-strength steel for automotive steel sheets is being developed to meet both the need to reduce vehicle weight in response to environmental regulations and the need to tighten collision safety standards due to tightening safety regulations. However, since strength and elongation have a trade-off relationship, there is a problem that formability decreases as strength increases, and various studies have been conducted to ensure formability of high-strength steel.
[0003] TRIP (Transformation Induced Plasticity) assisted steels (which utilize the TRIP phenomenon, which transforms retained austenite into martensite during the transformation of retained austenite within the microstructure) are being developed as third-generation steel sheets that can ensure high strength and high elongation. The physical properties of these TRIP assisted steels are determined by the phase stability and fraction of retained austenite that causes the TRIP phenomenon, so ensuring stable retained austenite within the microstructure is crucial in manufacturing steel.
[0004] Related prior art includes Korean patent application number 2018-0033119. Summary of the invention
[0005] Technical issues
[0006] Therefore, the present invention has been accomplished in view of the above-mentioned problems, and an object of the present invention is to provide a cold-rolled ultra-high strength low-carbon steel sheet having excellent formability and a method for manufacturing the same.
[0007] Technical Solution
[0008] According to one aspect of the present invention, there is provided a cold-rolled steel sheet, the cold-rolled steel sheet comprising 0.15 wt % to 0.20 wt % of carbon (C), 1.0 wt % to 2.0 wt % of silicon (Si), 1.5 wt % to 3.0 wt % of manganese (Mn), greater than 0 wt % and less than or equal to 0.02 wt % of phosphorus (P), greater than 0 wt % and less than or equal to 0.003 wt % of sulfur (S), 0.01 wt % to 0.3 wt % of aluminum (Al), greater than 0 wt % and less than or equal to 0.01 wt % of nitrogen (N), 48 / 14 wt % to 50 wt % of nitrogen (N). 0.1 wt. % titanium (Ti) ([N] is the content of nitrogen (wt. %)), the balance iron (Fe) and other inevitable impurities, wherein the final microstructure of the cold-rolled steel sheet consists of ferrite, acicular retained austenite, a martensite / austenite composite structure and blocky martensite; the area fraction of ferrite is 30 to 60%, the area fraction of acicular retained austenite is 5 to 12%, the area fraction of martensite / austenite composite structure is 25 to 50%, and the area fraction of blocky martensite is 5 to 12%; and the amount of carbon concentrated in the retained austenite is 1.1 wt. % or more.
[0009] Ferrite in the cold-rolled steel sheet may be composed of polygonal ferrite and acicular ferrite, and the area fraction of the acicular ferrite in the ferrite may be 40% or more.
[0010] The cold rolled steel sheet may have a tensile strength (TS) of 980 MPa to 1180 MPa and an elongation (El) of 23% to 25%.
[0011] According to another aspect of the present invention, there is provided a method for manufacturing a cold-rolled steel sheet, the method comprising the step (a) of reheating steel, the steel comprising 0.15 wt% to 0.20 wt% of carbon (C), 1.0 wt% to 2.0 wt% of silicon (Si), 1.5 wt% to 3.0 wt% of manganese (Mn), more than 0 wt% and less than or equal to 0.02 wt% of phosphorus (P), more than 0 wt% and less than or equal to 0.003 wt% of sulfur (S), 0.01 wt% to 0.3 wt% of aluminum (Al), more than 0 wt% and less than or equal to 0.01 wt% of nitrogen (N), 48 / 14·[N] wt% to 0.1 wt% of titanium (Ti) ([N] is the content of nitrogen (wt%)), and the remainder Iron (Fe) and other inevitable impurities; a step (b) of hot rolling the reheated steel; a step (c) of cold rolling the hot rolled steel; a first annealing step (d) of maintaining the cold rolled steel at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C) and cooling the cold rolled steel to a cooling end temperature of 340°C or less; and a second annealing step (e) of maintaining the steel at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C), cooling the steel to a cooling end temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C), and performing overaging, wherein the second annealing temperature is lower than the first annealing temperature.
[0012] In the method for manufacturing a cold-rolled steel sheet, step (a) may include the step of reheating the steel at 1180°C to 1300°C, step (b) may include the step of hot rolling at a finishing temperature of 850°C to 950°C and a coiling temperature of 450°C to 650°C, and step (c) may include the step of cold rolling at a reduction ratio of 40% to 70%.
[0013] In the method of manufacturing a cold-rolled steel sheet, step (d) may include a process of maintaining the cold-rolled steel at the primary annealing temperature for 30 to 120 seconds and cooling the cold-rolled steel to a cooling end point temperature of 340° C. or less at a cooling rate of 15° C. / s or more.
[0014] In the method of manufacturing a cold-rolled steel sheet, after performing step (d), the area fraction of ferrite in the microstructure of the steel may be 30% to 50%.
[0015] In the method for manufacturing a cold-rolled steel sheet, step (e) may include a process of maintaining the steel at a secondary annealing temperature for 30 seconds to 120 seconds, cooling the steel to a cooling endpoint temperature greater than or equal to a martensite transformation start temperature (Ms) and less than or equal to (a bainite transformation start temperature (Bs) - 15°C) at a cooling rate of 15°C / s or more, and performing overaging for 30 seconds to 300 seconds.
[0016] In the method for manufacturing a cold-rolled steel sheet, after performing step (e), the microstructure of the steel may be composed of ferrite, acicular retained austenite, a martensite / austenite composite structure and blocky martensite; and the area fraction of ferrite may be 30% to 60%, the area fraction of acicular retained austenite may be 5% to 12%, the area fraction of the martensite / austenite composite structure may be 25% to 50%, and the area fraction of blocky martensite may be 5% to 12%.
[0017] Beneficial effects
[0018] According to an embodiment of the present invention, a cold-rolled ultra-high strength low-carbon steel sheet with excellent formability and a method for manufacturing the same can be achieved. Specifically, by designing using low-carbon steel containing 0.2 wt% or less carbon content, excellent weldability can be ensured. During the heat treatment process, through multiple steps of redistributing alloying elements, a sufficient amount of carbon and manganese can be concentrated in austenite to achieve an excellent balance of strength and elongation. By ensuring a tensile strength of 980 MPa or more and an elongation of 23% or more, a cold-rolled ultra-high strength steel with excellent processability can be achieved.
[0019] In addition, the scope of the present invention is not limited to these effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The flowchart schematically shows a method for manufacturing a cold-rolled steel sheet according to an embodiment of the present invention.
[0021] Figure 2 Included are graphs showing overviews of (a) a first annealing process and (b) a second annealing process in a method of manufacturing a cold-rolled steel sheet according to an embodiment of the present invention.
[0022] Figure 3 is an image of the microstructure after the first annealing in Example 1 in the experimental example.
[0023] Figure 4 is an image of the microstructure after the second annealing in Example 1 in the experimental example.
[0024] Figure 5 is an image of the microstructure after the first annealing in Comparative Example 6 in the experimental example, Figure 6 is an image of the final microstructure in Comparative Example 7 in the experimental example, Figure 7 is an image of the final microstructure in Comparative Example 8 in the experimental example, Figure 8 is an image of the final microstructure in Comparative Example 9 in the experimental example, and Fig. 9Included are images of (a) acicular structure and (b) bulk structure after secondary annealing and overaging. DETAILED DESCRIPTION
[0025] A cold rolled steel sheet and a method for manufacturing the same according to an embodiment of the present invention will be described in detail. The terms described below are appropriately selected in consideration of their functions in the present invention, and the definitions of these terms should be based on the contents in this specification. Hereinafter, a cold rolled ultra-high strength low carbon steel sheet with excellent formability and a method for manufacturing the same will be described in detail.
[0026] Korean Patent Application No. 2018-0033119 proposes a method for manufacturing a steel containing tempered martensite and retained austenite (quenching and partitioning, Q&P) by rapid cooling and partitioning heat treatment after annealing steel. The advantage of Q&P steel is that even with 0.2 wt% carbon steel, physical properties including a tensile strength of 980 MPa or more and an elongation of 21% or more can be obtained. However, Q&P steel has a narrow process temperature window and has a large ductility deviation, making it difficult to stably ensure the high elongation required by the present invention.
[0027] Korean Patent Application Publication No. 2017-0113858 proposes a double annealing process as a method of ensuring a microstructure (complete structure) before final annealing to improve the ductility of steel by ensuring lath ferrite and retained austenite. However, in order to ensure a low-temperature structure with a volume fraction of 90% or more after the first annealing, single-phase annealing is performed, making it impossible to reliably ensure a tensile strength of 980 MPa or more in steel with a low carbon content. In addition, the life of the furnace may be shortened due to high-temperature annealing.
[0028] The present invention discloses a cold-rolled ultra-high strength steel sheet with excellent elongation suitable for automobile parts and a method for manufacturing the same, wherein the cold-rolled ultra-high strength steel sheet has a tensile strength of 980 MPa or more and an elongation of 23% or more. The microstructure of the cold-rolled steel sheet consists of polygonal ferrite with an area fraction of 20% or more and 50% or less, acicular ferrite with an area fraction of 40% or more, acicular residual austenite with an area fraction of 5% or more and 12% or less, a martensite / austenite composite structure with an area fraction of 5% or more, and a balance of bainite. In addition, the present invention discloses alloy amounts and heat treatment conditions suitable for ensuring target yield strength, tensile strength, and elongation.
[0029] Steel Plate
[0030] The cold rolled steel sheet according to the embodiment of the present invention is composed of 0.15 wt % to 0.20 wt % of carbon (C), 1.0 wt % to 2.0 wt % of silicon (Si), 1.5 wt % to 3.0 wt % of manganese (Mn), greater than 0 wt % and less than or equal to 0.02 wt % of phosphorus (P), greater than 0 wt % and less than or equal to 0.003 wt % of sulfur (S), 0.01 wt % to 0.3 wt % of aluminum (Al), greater than 0 wt % and less than or equal to 0.01 wt % of nitrogen (N), 48 / 14·[N] wt % to 0.1 wt % of titanium (Ti) ([N] is the content of nitrogen (wt %)), the remainder of iron (Fe), and other inevitable impurities.
[0031] The role and content of each component contained in the cold-rolled steel sheet are described below.
[0032] Carbon (C)
[0033] Adding carbon (C) is to ensure the strength of steel, and the strength increases with the increase of carbon content in the martensitic structure. In addition, carbon (C) combines with elements such as iron to form carbides, thereby improving strength and hardness. In the cold-rolled steel sheet according to an embodiment of the present invention, carbon (C) can be added in a content ratio of 0.15 weight % to 0.20 weight % of the total weight. When the content of carbon is less than 0.15 weight % of the total weight, the above effect may not be achieved, and sufficient strength may not be ensured. On the contrary, when the content of carbon exceeds 0.20 weight % of the total weight, weldability and processability may be reduced.
[0034] Silicon (Si)
[0035] Silicon (Si) is added to improve strength and inhibit carbide formation through the ferrite solid solution strengthening effect. In addition, silicon is a well-known ferrite stabilizing element, and ductility can be improved by increasing the ferrite fraction during cooling. In addition, silicon is a known element that can ensure strength by enriching austenite carbon to promote martensite formation. In addition, silicon is added together with aluminum as a deoxidizer to remove oxygen in steel in the steelmaking process, and can also have a solid solution strengthening effect. Silicon can be added in a content ratio of 1.0 wt % to 2.0 wt % of the total weight of the cold-rolled steel sheet according to an embodiment of the present invention. When the silicon content is less than 1.0 wt % of the total weight, ductility may not be ensured, and the above-mentioned silicon addition effect may not be properly achieved. On the contrary, when the silicon content exceeds 2.0 wt % of the total weight, oxides (such as Mn2SiO4) may be formed during the manufacturing method, impairing the plating properties, and increasing the carbon equivalent, which may reduce weldability. Furthermore, the surface quality may be degraded by the generation of red oxide scale during reheating and hot rolling, and the toughness and plastic workability may be reduced.
[0036] Manganese (Mn)
[0037] Manganese (Mn) contributes to improving strength by improving hardenability, promotes the formation of low temperature transformation phase, and provides the effect of improving strength by solid solution strengthening effect. Manganese can be added in a content ratio of 1.5 wt % to 3.0 wt % of the total weight of the cold rolled steel sheet according to an embodiment of the present invention. When the content of manganese is less than 1.5 wt %, the above-mentioned effect of ensuring strength may not be fully achieved. In addition, when the content of manganese exceeds 3.0 wt %, due to the formation or segregation of inclusions (such as MnS), processability and delayed fracture resistance may be reduced, and the carbon equivalent may increase, thereby reducing weldability.
[0038] Phosphorus (P)
[0039] Phosphorus (P) improves strength through a solid solution strengthening effect and can play a role in suppressing the formation of carbides. Phosphorus may be added in a content ratio of greater than 0 wt % and less than or equal to 0.02 wt % of the total weight of the cold-rolled steel sheet according to an embodiment of the present invention. When the content of phosphorus exceeds 0.02 wt %, the weld area becomes brittle and low-temperature embrittlement occurs, which reduces press formability and impact resistance.
[0040] Sulfur (S)
[0041] Sulfur (S) improves the machinability of steel by combining with manganese and titanium, and can improve machinability by forming fine MnS precipitates, but generally inhibits ductility and weldability. Sulfur may be added in a content ratio of greater than 0 wt% and less than or equal to 0.003 wt% of the total weight of the cold-rolled steel sheet according to an embodiment of the present invention. When the sulfur content exceeds 0.003 wt%, as the number of FeS inclusions or MnS inclusions increases, toughness and weldability decrease, machinability is poor, and high-temperature cracks may occur due to segregation during solidification during continuous casting.
[0042] Aluminum (Al)
[0043] Aluminum (Al) is an element mainly used as a deoxidizer. Aluminum promotes the formation of ferrite, improves elongation, inhibits the formation of carbides, and stabilizes austenite by increasing the carbon concentration in austenite. Aluminum (Al) is preferably added in a content ratio of 0.01 wt % to 0.3 wt % of the total weight of the cold-rolled steel sheet according to an embodiment of the present invention. When the content of aluminum (Al) is less than 0.01 wt %, the above-mentioned effect of adding aluminum may not be properly achieved. On the contrary, when the content of aluminum (Al) exceeds 0.3 wt %, aluminum inclusions increase, deteriorate the performance, concentrate on the surface of the steel sheet, deteriorate the plating properties, and form AlN in the slab, resulting in hot rolling cracks.
[0044] Nitrogen (N)
[0045] Nitrogen (N) is an element that has a solid solution strengthening effect and can improve the strength of steel plates, and is generally an element mixed from the atmosphere. During steelmaking, the nitrogen content must be controlled through a degassing process. When the nitrogen content exceeds 0.01 wt%, the weld area becomes brittle, low-temperature embrittlement occurs, press formability decreases, and impact resistance decreases.
[0046] Titanium (Ti)
[0047] Titanium (Ti) is a precipitation phase forming element, which has the effect of precipitating TiN and refining the grains. In particular, the nitrogen content in the steel can be reduced by the precipitation of TiN. It is preferably added in an amount of 48 / 14·[N] wt % to 0.1 wt %. When the titanium content is less than 48 / 14·[N] wt %, the effect of adding Ti may not be significant due to the small amount of TiC precipitated. When the titanium content exceeds 0.1 wt %, it is difficult to ensure strength by reducing the solid solubility of carbon in the matrix material.
[0048] As described above, the cold-rolled steel sheet having an alloy element composition according to an embodiment of the present invention may be a cold-rolled ultra-high strength steel sheet having a tensile strength of 980 MPa or more and an elongation of 23% or more and having excellent elongation. For example, the cold-rolled steel sheet may have a tensile strength (TS) of 980 MPa to 1180 MPa and an elongation (El) of 23% to 25%.
[0049] The final microstructure of the cold-rolled steel sheet consists of ferrite, acicular retained austenite, a martensite / austenite composite structure, and blocky martensite. The area fraction of ferrite is 30% to 60%, the area fraction of acicular retained austenite is 5% to 12%, the area fraction of martensite / austenite composite structure is 25% to 50%, and the area fraction of blocky martensite is 25% to 50%. The carbon content in the retained austenite is 1.1% by weight or more. Ferrite consists of polygonal ferrite and acicular ferrite, and in ferrite, the area fraction of acicular ferrite can be 40% or more.
[0050] Hereinafter, a method of manufacturing a cold-rolled steel sheet having the above-described composition and microstructure according to an embodiment of the present invention will be described.
[0051] Method for manufacturing steel plate
[0052] Figure 1 The flowchart schematically shows a method for manufacturing a cold-rolled steel sheet according to an embodiment of the present invention.
[0053] refer to Figure 1 , the method for manufacturing a steel plate according to an embodiment of the present invention sequentially includes the step (a) of reheating steel (S100), the steel comprising 0.15 wt% to 0.20 wt% of carbon (C), 1.0 wt% to 2.0 wt% of silicon (Si), 1.5 wt% to 3.0 wt% of manganese (Mn), more than 0 wt% and less than or equal to 0.02 wt% of phosphorus (P), more than 0 wt% and less than or equal to 0.003 wt% of sulfur (S), 0.01 wt% to 0.3 wt% of aluminum (Al), more than 0 wt% and less than or equal to 0.01 wt% of nitrogen (N), 48 / 14·[N] wt% to 0.1 wt% of titanium (Ti) ([N] is the content of nitrogen (wt%)), and the balance of iron (Fe). ) and other inevitable impurities; a step (b) of hot rolling the reheated steel (S200); a step (c) of cold rolling the hot rolled steel (S300); a first annealing step (d) of maintaining the cold rolled steel at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C) and cooling the cold rolled steel to a cooling end temperature of 340°C or less (S400); and a second annealing step (e) of maintaining the steel at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C), cooling the steel to a cooling end temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C), and performing overaging.
[0054] Step (a) (S100) may include the step of reheating the slab steel having the composition at 1180°C to 1300°C. The slab is manufactured in the form of a semi-finished product by continuously casting the molten steel obtained by the steelmaking process. Through the reheating process, the component segregation generated in the casting process is homogenized, and the semi-finished product is ready for hot rolling. When the slab reheating temperature (SRT) is 1180°C or lower, there is a problem that the segregation of the slab may not be fully reused. When the slab reheating temperature (SRT) exceeds 1300°C, the size of the austenite grains may increase and the process cost may increase. The reheating of the slab may be performed for 1 to 4 hours. When the reheating time is less than 1 hour, the reduction of segregants is not significant. When the reheating time exceeds 4 hours, the grain size and process cost may increase.
[0055] Step (b) (S200) is a step of hot rolling the reheated slab. Hot rolling is performed at a finishing exit temperature (FDT) of 850°C to 950°C. When the finishing exit temperature is lower than 850°C, the rolling load increases rapidly and productivity decreases. When the finishing exit temperature exceeds 950°C, the strength may decrease as the grain size increases. After hot rolling, cooling is performed at a temperature of 450°C to 650°C and then coiling is performed. When the coiling temperature is lower than 450°C, the shape of the hot-rolled coil becomes uneven and the strength increases, which increases the rolling load during cold rolling. When the coiling temperature exceeds 650°C, surface oxidation may cause defects in post-processing, an uneven microstructure may result due to the difference in cooling rate between the center and edge of the steel plate, and the interior of the grain may be oxidized.
[0056] Step (c) is a step of pickling the hot rolled coil to remove the surface oxide layer and performing cold rolling. The thickness reduction rate during cold rolling is about 40% to 70%. As the reduction rate increases, the formability may increase due to the microstructure refinement effect. When the reduction rate during cold rolling is less than 40%, it is difficult to obtain a uniform microstructure. When the reduction rate exceeds 70%, the rolling force increases and the process load increases.
[0057] After cold rolling, the first annealing process and the second annealing process are performed in sequence. That is, the cold-rolled steel sheet undergoes the first annealing and the second annealing, and is annealed twice in total. The heating rate from room temperature to the first or second annealing temperature section is not limited, and can follow the heating rate of a normal heating device.
[0058] Step (d) is a first annealing step including a process of maintaining the cold-rolled steel at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C) and cooling the cold-rolled steel to a cooling end point temperature of 340°C or less.
[0059] Step (d) is a step of annealing for 30 seconds to 120 seconds at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C) to ensure a dual-phase structure of ferrite and low-temperature phase. The first annealing process is a process for forming a desired complete structure to ensure a lath-shaped ferrite and needle-shaped austenite structure in the second annealing process. In this specification, "complete structure" refers to the microstructure of the steel manufactured by the first annealing S400. In the second annealing process, the low-temperature phase structure undergoes a reverse transformation to austenite, and a lath-shaped ferrite and austenite microstructure are formed. Here, the low-temperature phase structure refers to a martensite or bainite phase. This lath-shaped structure is characterized by ensuring high strength and high ductility. When annealing in the dual-phase temperature range, a redistribution of carbon and manganese occurs, carbon and manganese are enriched in the austenite region, and the phase stability of austenite is improved.
[0060] In order to meet the tensile properties of the steel of 0.2 wt% or less proposed in the present invention (including a tensile strength of 980 MPa or more and an elongation of 23% or more), in addition to conventional heat treatment, it is necessary to redistribute carbon and manganese into austenite to increase the strength of martensite, thereby ensuring sufficient tensile strength and improving the phase stability of retained austenite, thereby ensuring sufficient ductility. Therefore, it is desirable to perform the first annealing in the dual-phase temperature range. When the first annealing temperature exceeds Ac3, the austenite crystals become coarser due to high temperature annealing, and a large amount of austenite with low carbon content and manganese content is produced, making it difficult to ensure the tensile properties of the final steel. On the other hand, when the first annealing temperature is greater than or equal to Ac1 and less than (Ac1+30°C), after the first annealing process, the ferrite fraction in the microstructure exceeds 50%, resulting in an increase in soft and coarse polygonal ferrite in the final microstructure, making it difficult to ensure the tensile properties of the steel.
[0061] Therefore, after the first annealing process, the microstructure preferably shows a dual phase (DP) structure composed of ferrite and a low temperature phase. More preferably, in order to balance strength and ductility, the fraction of ferrite can be limited to 30% to 50% area fraction. When the steel sheet subjected to the first annealing is cooled to room temperature, in order to suppress the formation of polygonal ferrite that adversely affects physical properties during cooling and to ensure a low temperature martensitic structure, cooling may be performed at 15°C / s or more, preferably 25°C / s or more.
[0062] In addition, in an improved embodiment of the present invention, when the microstructure after the first annealing process is a dual phase (DP) structure consisting of ferrite and a low temperature phase and the fraction of ferrite is limited to an area fraction of 30% to 50%, the heat treatment temperature of the first annealing can be limited to greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C).
[0063] Step (e) is a second annealing step including maintaining the steel at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C), cooling the steel to a cooling end point temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C), and then performing an overaging process.
[0064] Step (e) is a step in which the martensitic structure produced in the first annealing process undergoes a reverse transformation to form lath-shaped ferrite and austenite. During the annealing process, redistribution of carbon and manganese to austenite and a reverse transformation of the first low-temperature phase occur. Therefore, it is desirable to increase the annealing time to ensure sufficient reverse transformation and alloy element redistribution. However, when the annealing time is excessively increased, there is a risk of reduced productivity, so the annealing holding time is limited to 30 seconds to 120 seconds.
[0065] The step is a step of cooling the second annealed steel sheet to a temperature between the martensite transformation start temperature (Ms) and the bainite transformation start temperature (Bs) and maintaining the temperature for 30 seconds to 300 seconds to induce redistribution of carbon and manganese alloy elements to improve the phase stability of retained austenite. When cooled to a cooling end temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C), when the cooling rate is less than 15°C / s, polygonal ferrite is generated during the cooling process, resulting in poor tensile properties of the final steel. Therefore, the cooling rate is 15°C / s or more, preferably 25°C / s or more. When the cooling end temperature is higher than (bainite transformation start temperature (Bs)-15°C), ferrite or pearlite is generated in the holding step, thereby reducing strength and elongation. When the cooling end temperature is lower than the bainite transformation start temperature (Bs), bainite transformation and carbon redistribution do not occur in a balanced manner in the high temperature bainite form interval. When the cooling end temperature is lower than the martensite transformation start temperature (Ms), new martensite is generated by cooling, thereby significantly improving the strength of the steel. However, the residual austenite is reduced, so that the sufficient elongation of 23% or more required by the present invention cannot be ensured. Therefore, the cooling end temperature is preferably a temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C). After cooling to the cooling end temperature, the temperature is maintained for 30 seconds to 300 seconds to perform additional redistribution of carbon and manganese, and then cooled to room temperature. At this time, there is no specific limitation on the cooling rate to room temperature, but for productivity, it is preferably 10°C / s or more.
[0066] In addition, in the method for manufacturing a cold-rolled steel sheet according to the present invention, the second annealing temperature may be lower than the first annealing temperature. When the second annealing temperature is higher than the first annealing temperature, the fraction of austenite produced in the second annealing S500 is higher than the low-temperature phase fraction of the structure after the first annealing S400. Austenite (which undergoes reverse transformation in the low-temperature phase) exhibits a layered structure of acicular ferrite and austenite. However, due to the high annealing temperature, the excessively produced austenite develops into a block, and as a result, the fraction of blocky austenite increases in the final microstructure, thereby significantly improving the tensile strength of the steel and reducing the elongation of the steel.
[0067] The microstructure of the steel finally achieved by the above heat treatment process is composed of ferrite, acicular retained austenite, a martensite / austenite composite structure and blocky martensite. The area fraction of ferrite may be 30% to 60%, the area fraction of acicular retained austenite may be 5% to 12%, the area fraction of martensite / austenite composite structure may be 25% to 50%, and the area fraction of blocky martensite may be 5% to 12%.
[0068] Within the range of the composition described in the present invention, the above-mentioned heat treatment process and the steel composed of the microstructure obtained by the heat treatment process can realize a low carbon cold-rolled ultra-high strength steel sheet with excellent formability by having a tensile strength (TS) of 980MPa to 1180MPa and an elongation (El) of 23% to 25%.
[0069] Hereinafter, the above-mentioned annealing process is described with reference to the accompanying drawings.
[0070] Figure 2 Included are graphs showing overviews of (a) a first annealing process S400 and (b) a second annealing process S500 in the method of manufacturing a cold-rolled steel sheet according to an embodiment of the present invention.
[0071] First annealing S400
[0072] refer to Figure 2 A, interval ab corresponds to a step of maintaining at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C), interval bc is the first half of the cooling interval and corresponds to a slow cooling process, interval cd is the second half of the cooling interval and corresponds to a fast cooling process, and interval de corresponds to an over-aging process. In a modified embodiment of the present invention, the slow cooling process of interval bc and the over-aging process of interval de can be omitted.
[0073] The first annealing process can be maintained for 30 seconds to 120 seconds at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C). When the carbon content proposed in this embodiment is 0.2 wt% or less, the redistribution of alloying elements must be increased compared to existing steel types to ensure the tensile strength of the steel. Therefore, the first annealing process is carried out in a dual-phase temperature range to induce a primary redistribution of alloying elements. At this time, when the annealing temperature is too low, a large amount of polygonal ferrite is formed in the microstructure after the first annealing process, making it difficult to ensure sufficient tensile strength. When the annealing temperature exceeds (Ac3-30°C), high temperature annealing causes grain coarsening and an increase in the fraction of poor austenite with low alloy elements, making it difficult to achieve the target tensile properties. When the holding time exceeds 120 seconds, the grain size may become coarse and the productivity may decrease. The annealed cold-rolled steel is cooled to a temperature of 340°C or less at a cooling rate of 15°C / s or more. At this time, when the cooling end temperature exceeds 340°C, it is difficult to obtain a lath structure in the second annealing process due to carbide precipitation. When the cooling rate is less than 15°C / s, a large amount of polygonal ferrite will be generated during the cooling process, which is not conducive to ensuring tensile strength.
[0074] The interval bc is a step of slowly cooling the annealed steel sheet. When cooling the annealed steel sheet, a slow cooling interval may be included depending on the heat treatment equipment. When the slow cooling interval is included, there is no specific limitation on the slow cooling end temperature or the cooling rate, but in order to prevent a large amount of polygonal ferrite from being generated during the cooling process, preferably, the slow cooling end temperature may be 740°C or higher, and the cooling rate may be -5°C / s or more.
[0075] The interval cd is the latter half of the cooling interval and corresponds to a rapid cooling process, and is a step of cooling the steel plate cooled by the slow cooling process to a temperature of 340°C or lower. When cooling the first annealed steel plate or the first cooled steel plate, in order to suppress the formation of polygonal ferrite that has a negative impact on physical properties and form bainite or martensite (which is a low temperature phase), cooling is performed at a cooling rate of -15°C / s or more, preferably 25°C / s or more. The cooling rate is maintained to a temperature of the martensitic transformation start temperature (Ms) or lower (expressed as the following equation (1)). Then, cooling is performed to room temperature through the over-aging interval of the equipment. Alternatively, by omitting the over-aging interval, cooling can be performed directly to room temperature.
[0076] Equation (1)
[0077] Ms(℃)=491.1-302.6[C]-14.5[Si]-30.6[Mn]-16.6[Ni]-8.9[Cr]+2.4[Mo]-11.3[Cu]+8.58[Co]+7.4[W]
[0078] Here, [C], [Si], [Mn], [Ni], [Cr], [Mo], [Cu], [Co], and [W] represent the mass % of carbon, silicon, manganese, nickel, chromium, molybdenum, copper, cobalt, and tungsten in steel.
[0079] Second annealing S500
[0080] refer to Figure 2 B, interval pq corresponds to a step of maintaining at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C). Interval qr is the first half of the cooling interval and corresponds to the slow cooling interval. Interval rs is the second half of the cooling interval and corresponds to the fast cooling interval. Interval st corresponds to the over-aging interval. In addition, Figure 2 In the second annealing process shown in B, the dotted line profile between the bainite transformation start temperature (Bs) and the martensite transformation start temperature (Ms) corresponds to the case where the plating process is performed in a plating bath.
[0081] The second annealing process can be maintained at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C) for 30 seconds to 120 seconds. In addition, the second annealing temperature can be lower than the first annealing temperature. A step of performing dual-phase annealing for 30 seconds to 120 seconds at a temperature greater than or equal to Ac1 and lower than the first annealing temperature is performed. This step is a step in which the low-temperature phase structure generated in the first annealing S400 is reversed to form lath ferrite and austenite. During the annealing process, the reverse transformation of the first low-temperature phase and the redistribution of carbon (C) and manganese (Mn) to austenite occur. Therefore, a longer annealing time is desired for sufficient reverse transformation and alloy element redistribution. However, when the annealing time is excessively increased, there is a risk of reduced productivity, so the annealing holding time is limited to 30 seconds to 120 seconds. When the annealing temperature of the second annealing S500 is higher than the annealing temperature of the first annealing S400, the austenite fraction generated in the second annealing is greater than the low-temperature phase fraction in the complete structure. Therefore, the development of lath austenite that undergoes reverse transformation in the low temperature phase is suppressed, and block austenite is produced in an excessive fraction. This block austenite reduces the phase stability of austenite by reducing the carbon (C) and manganese (Mn) redistributed to the lath austenite. This hinders the effectiveness of the first annealing S400 in producing the lath-shaped structure required to ensure the elongation sought to be achieved in the present invention. Therefore, the second annealing S500 is preferably performed at a temperature lower than the first annealing S400.
[0082] Then, cooling is performed to a cooling endpoint temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs) - 15°C) at a cooling rate of 15°C / s or greater, and overaging is performed for 30 to 300 seconds to induce redistribution of carbon (C) and manganese (Mn) alloying elements to improve the phase stability of retained austenite.
[0083] The bainite transformation start temperature (Bs) can be expressed by the following equation (2).
[0084] Equation (2)
[0085] Bs(℃)=656-57.7[C]-75[Si]-35[Mn]-15.3[Ni]-34[Cr]-41.2[Mo]
[0086] Here, [C], [Si], [Mn], [Ni], [Cr], and [Mo] represent the mass % of carbon, silicon, manganese, nickel, chromium, and molybdenum in steel.
[0087] When cooled to a temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs) - 15°C), when the cooling rate is less than 15°C / s, polygonal ferrite is generated during cooling, resulting in poor tensile properties of the final steel. Therefore, the cooling rate should be 15°C / s or more, preferably 25°C / s or more.
[0088] When the cooling end temperature is less than or equal to the bainite transformation start temperature (Bs) and greater than (bainite transformation start temperature (Bs)-15°C), austenite is transformed into ferrite or pearlite during the holding step, resulting in a decrease in strength and elongation. When the cooling end temperature is lower than the bainite transformation start temperature (Bs), it is difficult to ensure the phase stability of the retained austenite due to the lack of carbon redistribution. On the contrary, when the cooling end temperature is lower than the martensite transformation start temperature (Ms), rash martensite is produced, which significantly improves the strength of the steel, but on the other hand, the retained austenite is reduced, making it impossible to ensure a sufficient elongation greater than 23% (which is the goal of the present invention). In addition, when the retention time is less than 30 seconds, the redistribution effect may be reduced due to insufficient redistribution time, and when the holding time exceeds 300 seconds, the productivity may be reduced.
[0089] After cooling to the cooling end temperature, overaging is performed for 30 seconds to 300 seconds to redistribute carbon (C) and manganese (Mn), and then cooling is performed to room temperature. During the overaging process, the temperature does not need to be isothermally maintained at the cooling end temperature. Cooling can be performed as needed, but the temperature must be Ms or higher to prevent the formation of new martensite. In addition, there is no specific limitation on the cooling rate to room temperature, but for productivity, it is preferably 10°C / s or greater. The redistribution effect of carbon (C) and manganese (Mn) during the overaging process varies depending on the austenite shape, and the redistribution effect of the needle shape is greater than that of the block shape. In the needle shape, the diffusion distance of carbon (C) and manganese (Mn) is shorter, so diffusion is more likely to occur in the same time. As Fig. 9 As shown in Table 1, as a result of analyzing the contents of carbon (C) and manganese (Mn) in the needle-shaped structure and the block-shaped structure after overaging, it was confirmed that more carbon (C) and manganese (Mn) thickening occurred in the needle-shaped structure. Therefore, in the microstructure after the final cooling, the needle-shaped austenite remains as a martensite / austenite composite structure, and the block-shaped austenite remains as a block-shaped martensite.
[0090] [Table 1]
[0091] weight% acicular Block Carbon (C) 0.6±0.05 0.3±0.05 Manganese (Mn) 3.5±0.5 2.25±0.25
[0092] According to the cold-rolled steel sheet and the manufacturing method thereof according to the technical idea of the present invention, excellent weldability can be ensured by designing using low-carbon steel containing 0.2 wt% or less carbon content. During the heat treatment process, through multiple steps of redistributing alloy elements, sufficient amounts of carbon (C) and manganese (Mn) can be concentrated in austenite to achieve an excellent balance of strength and elongation. By ensuring a tensile strength of 980 MPa or more and an elongation of 23% or more, a cold-rolled ultra-high strength steel with excellent processability can be provided.
[0093] Experimental Examples
[0094] Hereinafter, in order to help understand the present invention, preferred experimental examples are shown. However, the following experimental examples are only intended to help understand the present invention, and the present invention is not limited to the following experimental examples.
[0095] 1. Preparation of samples
[0096] In this experimental example, samples having the alloy element compositions (unit: weight %) shown in Table 2 were provided.
[0097] [Table 2]
[0098] C Si Mn P S Al Ti N Fe 0.18 1.70 2.30 0.01 0.001 0.03 0.015 0.003 margin
[0099] The composition of Table 2, which is the composition of the cold-rolled steel sheet according to the embodiment of the present invention, includes 0.15 wt% to 0.20 wt% of carbon (C), 1.0 wt% to 2.0 wt% of silicon (Si), 1.5 wt% to 3.0 wt% of manganese (Mn), more than 0 wt% and less than 0.02 wt% of phosphorus (P), more than 0 wt% and less than 0.003 wt% of sulfur (S), 0.01 wt% to 0.3 wt% of aluminum (Al), more than 0 wt% and less than 0.01 wt% of
[0100] % by weight of nitrogen (N), 48 / 14·[N] wt% to 0.1 wt% of titanium (Ti) ([N] is the content of nitrogen (wt%)) and the balance of iron (Fe). According to the composition of Table 2, the bainite transformation start temperature (Bs) is 437.6°C, and the martensite transformation start temperature (Ms) is 341.6°C.
[0101] 5 Calculate the temperature using the following relationship.
[0102] Bs(℃)=656-57.7[C]-75[Si]-35[Mn]-15.3[Ni]-34[Cr]-41.2[Mo]
[0103] Ms(℃)=491.1-302.6[C]-14.5[Si]-30.6[Mn]-16.6[Ni]-8.9[Cr]+2.4[Mo]
[0104] -11.3[Cu]+8.58[Co]+7.4[W]
[0105] Furthermore, according to the composition in Table 2, the Ac1 temperature is 754°C, and the Ac3 temperature is 10 900℃.
[0106] In the experimental example of the present invention, the steel having the composition was reheated at 1250° C. for 4 hours, hot rolled to a thickness of 3.5 mm at a finishing outlet temperature (FDT) of 850° C.,
[0107] Then, the steel sheet is coiled at a coiling temperature of 600°C. Then, the surface oxide scale is removed by pickling.
[0108] And cold rolled to a thickness of 1.2 mm. Then, according to Figure 2 Disclosed configuration, for cold rolled steel 15 The plates were heat treated twice in succession.
[0109] 2. Process conditions and physical property evaluation
[0110] Table 3 shows the process conditions of the first annealing and the second annealing applied in the experimental examples of the present invention.
[0111] [Table 3]
[0112]
[0113] In Table 3, item A is the annealing temperature of the first annealing process S400, and corresponds to Figure 2 Item B is the annealing time of the first annealing process S400, and corresponds to Figure 2 Item C is the final temperature of the slow cooling of the first annealing process S400, and corresponds to the temperature at point c, which is Figure 2 Item D is the final temperature of the slow cooling process of interval bc in A. Item D is the final temperature of the rapid cooling of the first annealing process S400, and corresponds to the temperature at point d, which is Figure 2 The final temperature of the rapid cooling process in the interval cd in A. Item E is the over-aging time of the first annealing process S400, and corresponds to Figure 2 The process time of the over-aging process in the interval de in A. In addition, item F in Table 3 is the annealing temperature of the second annealing process S500, and corresponds to Figure 2 Item G is the annealing time of the second annealing process S500 and corresponds to Figure 2 Item H is the final temperature of the rapid cooling of the second annealing process S500, and corresponds to the temperature at point s, which is Figure 2 The final temperature of the rapid cooling process in interval rs in B. Item I is the final temperature of the overaging process S500 of the second annealing process, and corresponds to the temperature at point t, which is Figure 2 The final temperature of the overaging process in interval st in B. Item J is the overaging time of the second annealing process S500 and corresponds to Figure 2 The process time of the aging process in interval st in B.
[0114] [Table 4]
[0115]
[0116] Table 4 shows the area fraction (unit: %) of the microstructure and the amount of carbon concentrated in the retained austenite (unit: weight %) in the experimental examples of the present invention. The microstructure was analyzed using a scanning electron microscope (SEM), and XRD analysis was used to analyze the retained austenite fraction and the carbon content in the retained austenite. In Table 4, Item A is the area fraction of the ferrite phase achieved after the first annealing, Item B is the area fraction of the low temperature phase achieved after the first annealing, Item C is the area fraction of the ferrite phase achieved after the second annealing, Item D is the area fraction of polygonal ferrite in ferrite achieved after the second annealing, Item E is the area fraction of acicular ferrite in ferrite achieved after the second annealing, Item F is the area fraction of acicular retained austenite achieved after the second annealing, Item G is the area fraction of the martensite / austenite composite structure achieved after the second annealing, Item H is the area fraction of blocky martensite achieved after the second annealing, and Item I is the amount of carbon concentrated in the retained austenite achieved after the second annealing.
[0117] Table 5 shows the tensile properties in the experimental examples of the present invention. The tensile properties were evaluated by conducting a tensile test using Zwick / Roell Corp Z100 according to KS No. 5 standard.
[0118] In Table 5, the item TS represents the tensile strength (unit: MPa), the item T.El represents the elongation (unit: %), and the item TS×T.El represents the product of the tensile strength and the elongation (unit: MPa%).
[0119] [Table 5]
[0120]
[0121]
[0122] Referring to Tables 2 to 5, in the case of Examples 1 to 4, by appropriately performing the first annealing S400 and the second annealing S500 suggested by the present invention, the tensile strength of 980 MPa or more (e.g., 980 MPa to 1180 MPa), the elongation of 23% or more (e.g., 23% to 25%), and the tensile property of TS×E1 22000 MPa% or more to be achieved in the present invention are satisfied. Figure 3 , the microstructure (i.e., complete structure) after the first annealing S400 in Example 1 is composed of 43% ferrite and 57% low-temperature phase, which meets the conditions of the present invention (area fraction of ferrite: 30% to 50%). The microstructure after the second annealing S500 in Example 1 is similar to Figure 4It can be confirmed that ferrite, acicular retained austenite, a martensite / austenite composite structure, and massive martensite are composed of the target fractions of the present invention.
[0123] In Comparative Examples 1 to 4, the first annealing S400 was performed at a dual-phase temperature of 850°C, and a sufficient amount of ferrite (45%) was ensured in the microstructure after the first annealing. However, in the second annealing S500, the redistribution of alloy elements did not proceed smoothly, and the residual austenite fraction and phase stability were not sufficiently ensured. Therefore, the tensile strength was sufficiently high (over 1000 MPa), but the elongation was significantly less than 23% expected to be achieved in the present invention.
[0124] Specifically, in the case of Comparative Examples 1 and 2, in the second annealing S500, the cooling end temperature is higher than the bainite transformation start temperature (Bs), so the redistribution of carbon (C) and manganese (Mn) is ineffective during the holding time after the cooling end. The elongation does not reach the target (23% or more).
[0125] In Comparative Example 3, as in Examples 1 and 2, cooling is completed at an appropriate temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs) - 15°C). However, the overaging time is short (less than 30 seconds), so sufficient redistribution is not achieved, and the elongation is lower than the target (greater than 23%). In Example 2, the holding time is increased in the second annealing S500 compared to Comparative Example 3. It can be seen that the redistribution of carbon (C) and manganese (Mn) is fully achieved, and the elongation is significantly improved, and a sufficient holding time is required to improve the elongation.
[0126] In Comparative Example 4, the cooling final temperature in the second annealing S500 is lower than the martensite transformation start temperature (Ms). At the end of cooling, martensite is formed, and the austenite fraction is reduced, and due to the low temperature, the redistribution of carbon (C) and manganese (Mn) is ineffective, so the elongation is lower than the target value (23% or more).
[0127] In Comparative Examples 5, 6 and 7, in the first annealing S400, the annealing temperature is high, so the ferrite fractions in the microstructure after the first annealing are 6% and 0%, respectively, which are outside the range (30% to 50%) proposed in the present invention.
[0128] Reference shows the complete structure after the first annealing S400 in Comparative Example 6 Figure 5, by performing single-phase annealing, it can be confirmed that the complete structure consists of the low-temperature phase after the first annealing S400. In this way, as the annealing temperature of the first annealing S400 increases, the ferrite fraction in the complete structure decreases. As the low-temperature phase fraction increases, the polygonal ferrite in the final microstructure after the second annealing S500 decreases, the fractions of acicular ferrite and retained austenite increase, and the fraction of massive martensite decreases.
[0129] The final microstructure of the reference example 7 is shown in FIG. Figure 6 The overall microstructure consists of acicular ferrite, a martensite / austenite composite structure and residual austenite. Since there is very little blocky martensite that contributes to the increase in strength, in Comparative Examples 5 and 7, the elongation meets the target value of the present invention (23% or more), but the tensile strength does not meet the requirements.
[0130] In Comparative Example 6, in the second annealing S500, the cooling final temperature is set to 440°C, which is higher than the bainite transformation start temperature (Bs), and the redistribution of carbon (C) and manganese (Mn) after the cooling is completed is reduced to ensure a tensile strength higher than 1022 MPa. However, due to the lack of redistribution, the elongation is less than the target value (23% or more).
[0131] In Comparative Example 8, the annealing temperature of the second annealing S500 (second annealing temperature) is higher than the annealing temperature of the first annealing S400 (first annealing temperature), which is contrary to the heat treatment method proposed in the present invention. When the second annealing temperature is higher than the first annealing temperature, the fraction of austenite produced in the second annealing S500 is higher than the low-temperature phase fraction of the structure after the first annealing S400. The austenite that undergoes reverse transformation in the low-temperature phase appears as a layered structure of acicular ferrite and austenite, but the austenite excessively produced due to the high annealing temperature develops into a block. Therefore, in the final microstructure, the fraction of blocky martensite increases, thereby significantly improving the tensile strength of the steel, but reducing the elongation (see Figure 7 ).
[0132] Comparative Example 9 is a case where only conventional one-time annealing is performed, and as Figure 8 As shown, a microstructure consisting of massive bainite, martensite, and ferrite appears. High tensile strength and low elongation are observed due to the high massive martensite fraction, low martensite / austenite composite structure, and retained austenite fraction.
[0133] According to the experimental embodiments described above, when a dual-phase structure consisting of ferrite and a low-temperature phase is not ensured in the first annealing S400, or when acicular ferrite and austenite are not properly ensured in the second annealing S500, it is difficult to ensure the physical balance between tensile strength and elongation required by the present invention.
[0134] Although the present invention has been described with reference to the embodiments, various changes or modifications may be made by those skilled in the art. As long as these changes and modifications do not depart from the scope of the present invention, it can be said that they belong to the present invention. Therefore, the scope of the present invention should be determined by the claims described below.
Claims
1. A cold-rolled steel sheet, comprising 0.15 wt % to 0.20 wt % of carbon (C), 1.0 wt % to 2.0 wt % of silicon (Si), 1.5 wt % to 3.0 wt % of manganese (Mn), more than 0 wt % to less than or equal to 0.02 wt % of phosphorus (P), more than 0 wt % to less than or equal to 0.003 wt % of sulfur (S), 0.01 wt % to 0.3 wt % of aluminum (Al), more than 0 wt % to less than or equal to 0.01 wt % of nitrogen (N), 48 / 14·[N] wt % to 0.1 wt % of titanium (Ti) ([N] is the content of nitrogen (wt %)), the remainder of iron (Fe), and other inevitable impurities, in, The final microstructure of the cold-rolled steel sheet consists of ferrite, acicular retained austenite, a martensite / austenite composite structure and blocky martensite; The area fraction of ferrite is 30% to 60%, the area fraction of acicular retained austenite is 5% to 12%, the area fraction of martensite / austenite composite structure is 25% to 50%, and the area fraction of blocky martensite is 5% to 12%, and The amount of carbon concentrated in the retained austenite is 1.1 wt% or more.
2. The cold-rolled steel sheet according to claim 1, wherein: The ferrite is composed of polygonal ferrite and acicular ferrite, and the area fraction of the acicular ferrite in the ferrite is 40% or more.
3. The cold-rolled steel sheet according to claim 1, wherein: The cold rolled steel sheet has a tensile strength (TS) of 980 MPa to 1180 MPa and an elongation (El) of 23% to 25%.
4. A method for manufacturing a cold-rolled steel sheet, the method comprising: Step (a) of reheating steel, the steel comprising 0.15 wt% to 0.20 wt% of carbon (C), 1.0 wt% to 2.0 wt% of silicon (Si), 1.5 wt% to 3.0 wt% of manganese (Mn), more than 0 wt% and less than or equal to 0.02 wt% of phosphorus (P), more than 0 wt% and less than or equal to 0.003 wt% of sulfur (S), 0.01 wt% to 0.3 wt% of aluminum (Al), more than 0 wt% and less than or equal to 0.01 wt% of nitrogen (N), 48 / 14·[N] wt% to 0.1 wt% of titanium (Ti) ([N] is the content of nitrogen (wt%)), the balance of iron (Fe) and other inevitable impurities; step (b) of hot rolling the reheated steel; step (c) of cold rolling the hot rolled steel; a first annealing step (d) of maintaining the cold-rolled steel at a first annealing temperature greater than or equal to (Ac1+30°C) and less than or equal to (Ac3-30°C) and cooling the cold-rolled steel to a cooling end point temperature of 340°C or less; and A second annealing step (e) of maintaining the steel at a second annealing temperature greater than or equal to Ac1 and less than or equal to (Ac3-30°C), cooling the steel to a cooling end point temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs)-15°C), and performing overaging, Wherein, the second annealing temperature is lower than the first annealing temperature.
5. The method according to claim 4, wherein: Step (a) comprises the step of reheating the steel at 1180°C to 1300°C, Step (b) comprises the step of hot rolling at a finishing rolling temperature of 850°C to 950°C and a coiling temperature of 450°C to 650°C, and The step (c) includes the step of cold rolling at a reduction ratio of 40% to 70%.
6. The method according to claim 4, wherein: The step (d) includes a process of maintaining the cold-rolled steel at the primary annealing temperature for 30 to 120 seconds and cooling the cold-rolled steel to a cooling end point temperature of 340° C. or less at a cooling rate of 15° C. / s or more.
7. The method according to claim 6, wherein: After performing step (d), the area fraction of ferrite in the microstructure of the steel is 30% to 50%.
8. The method according to claim 4, wherein: Step (e) includes a process of maintaining the steel at the secondary annealing temperature for 30 to 120 seconds, cooling the steel at a cooling rate of 15°C / s or more to a cooling end point temperature greater than or equal to the martensite transformation start temperature (Ms) and less than or equal to (bainite transformation start temperature (Bs) - 15°C), and performing overaging for 30 to 300 seconds.
9. The method according to claim 8, wherein: After performing step (e), the microstructure of the steel consists of ferrite, acicular retained austenite, a martensite / austenite composite structure and massive martensite; and The area fraction of the ferrite is 30% to 60%, the area fraction of the acicular retained austenite is 5% to 12%, the area fraction of the martensite / austenite composite structure is 25% to 50%, and the area fraction of the blocky martensite is 5% to 12%.
